Lethal Images: Analyzing Extremist Visual Propaganda from ISIS and Beyond. Issue 4 (5th December 2019) - Baele, Stephane J; Boyd, Katharine A; Coan, Travis G
Abstract: Violent extremist groups regularly use pictures in their propaganda. This practice, however, remains insufficiently understood. Conceptualizing visual images as amplifiers of narratives and emotions, the present article offers an original theoretical framework and measurement method for examining the synchronic and diachronic study of the manipulative use of images by violent extremist groups. We illustrate this framework and method with a systematic analysis of the 2, 058 pictures contained in the Islamic State's propaganda magazines targeting Western audiences, exposing the "visual style" of the group, and highlighting the trends and shifts in the evolution of this style following developments on the ground.